Lesson learned from the assessment of planned converted CO2 injection well integrity in Indonesia – CCUS project - B.T.H. Marbun; S.Z. Sinaga; B. Purbantanu; D. Santoso; W.G.A. Kadir; R. Sule; D.E. Prasetyo; H. Prabowo; D. Susilo; F.R. Firmansyah; J.M. Palilu; W. Saprudin; et al. (Heliyon, 2023)
The risk of CO2 leakage from carbon capture, utilization, and storage (CCUS) wells and geological storage sites must be properly assessed before the implementation of CO2 injection. According to ISO 27914 and ISO/FDIS 27916, the design and construction of an injection well needs to guarantee safety and ability to contain the stored CO2 over a long-term period. However, these standards alone were inadequate to evaluate the well integrity due to the need to specify criteria, duration of measurement, and range of measurement parameters of the available tools according to industries’ best practices.The methodology used in the study adapted applicable and readily-available international standards, field experiences, and lessons learned that could be used to support the construction of new and/or the conversion of existing oil and gas wells into CO2 injection wells. This study focused on Jepon-1 in Gundih field, Indonesia, an abandoned oil and gas well. Its actual conditions, well integrity, capabilities of the equipment used in the workover and logging operations, and its limitations in checking the conditions of various crucial aspects of integrity, were evaluated. The results showed that the application of the international standards could not fulfill all the detailed requirements of integrity evaluation of the JPN-1 well due to its particular condition and situation. Other field experiences needed to be adapted, improved, and incorporated in the integrity evaluation of this well. Additionally, longer duration of measurement and more accurate and sensitive logging evaluation tools, combined with temperature logging tools, are required to detect leakage that could not be identified by the commercial tools used in this well.The result of this well integrity study will be used as a fundamental basis for constructing CCUS well regulations by the Government and stakeholders.